P2X7-deficiency improves plasticity and cognitive abilities in a mouse model of Tauopathy. (November 2021) - Carvalho, Kevin; Martin, Elodie; Ces, Aurélia; Sarrazin, Nadège; Lagouge-Roussey, Pauline; Nous, Caroline; Boucherit, Leyna; Youssef, Ihsen; Prigent, Annick; Faivre, Emilie; Eddarkaoui, Sabiha; Gauvrit, Thibaut; et al.
Highlights: The purinergic receptor P2X7 is overexpressed in the brain of patients with various Tauopathies. P2X7 contributes to Tau–related neuroinflammation, in part via CCL4 production, in Thy-Tau22 mice. P2X7-deficiency rescued long-term synaptic plasticity and hippocampal-dependent spatial memory. Abstract: Alzheimer's disease is the most common form of dementia characterized by intracellular aggregates of hyperphosphorylated Tau protein and extracellular accumulation of amyloid β (Aβ) peptides. We previously demonstrated that the purinergic receptor P2X7 (P2X7) plays a major role in Aβ-mediated neurodegeneration but the relationship between P2X7 and Tau remained overlooked. Such a link was supported by cortical upregulation of P2X7 in patients with various type of frontotemporal lobar degeneration, including mutation in the Tau-coding gene, MAPT, as well as in the brain of a Tauopathy mouse model (THY-Tau22). Subsequent phenotype analysis of P2X7-deficient Tau mice revealed the instrumental impact of this purinergic receptor. Indeed, while P2X7-deficiency had a moderate effect on Tau pathology itself, we observed a significant reduction of microglia activation and of Tau-related inflammatory mediators, particularly CCL4. Importantly, P2X7 deletion ultimately rescued synaptic plasticity and memory impairments of Tau mice. Altogether, the present data support a contributory role of P2X7 dysregulation on processes governing Tau-induced brain anomalies. Due to the convergent role of P2X7 blockade in both Aβ and Tau background, P2X7 inhibitors might prove to be ideal candidate drugs to curb the devastating cognitive decline in Alzheimer's disease and Tauopathies.